Analisis Pengembangan Bisnis UD. Sinar Harapan Melalui Pendekatan Business Model Canvas - Zulistiani; Jhosia Brillianda Adma Deanta (Universitas Indo Global Mandiri, 2023)
Every company must use a strategy to develop its business. One way to compete is to create a new strategy so that the company has a good and appropriate business model. The condition of the company is used as a tool in developing its business through a business model. The business model aims to prioritize value as part of technology development management. The business model used is the Business Model Canvas, which can build business activities and business models. UD Sinar Harapan is a company that produces crackers. The company seeks to implement strategic management in the business it runs. The purpose of this study is to determine the implementation of the Business Model Canvas, SWOT analysis, and business development strategies that should be applied to UD Sinar Harapan. This research was conducted using qualitative research methods and descriptive research types. This study uses five informants, namely, business owners, employees, and three customers of UD. Rays of hope Based on the results of the data obtained, it is known that UD. Sinar Harapan has not fully implemented the Business Model Canvas. However, there are five blocks that have been used, namely value proposition, channel, customer relationship, revenue stream, and key activity. UD. Sinar Harapan also found the need for a business development strategy that could be implemented through a SWOT analysis by increasing the number of variants, making brand labels on each package, and reproducing them online through a media network so that more subscribers will recognize it. Keywords: Development strategy, Business model canvas, SWOT analysis